Beyond the Context of Cultural Confidence: A Study of Communication Competence of the Chinese School - Tang, Hai; Gong, Xiaobin; Qi, Lihong (Advances in Social Sciences Research Journal, 2022)
Chinese animated films such as Monkey King: Hero is Back in 2015, Big Fish & Begonia in 2016 and Ne Zha: I am the Destiny in 2019 won higher box office and they achieved a similar popularity as the Wolf Warriors (2015 and 2017) in China’s film market. Perhaps partially because these animations bring audience a sense of familiarization such as they reveal popular culture and collective beliefs (i.e., “I’m the Destiny” as a slogan) to promote cultural identity. On the other hand, the making of Chinese animated films has been gradually getting mature in narration, adaptation, and creation. Both the production mode and the industrial scope have been formed to compete with Japanese anime and American cartoons. Though there are still many problems in making Chinese animations, Chinese School has been working on interpretating and deconstructing the essence of Chinese culture in their animated works. This attitude also marks Chinese School’s determination to disseminate Chinese culture so as to rebuild its confidence towards the animation world.